Quality‐based pharmacokinetic model selection on DCE‐MRI for characterizing orbital lesions. Issue 5 (15th April 2019) - Lecler, Augustin; Balvay, Daniel; Cuenod, Charles‐André; Marais, Louise; Zmuda, Mathieu; Sadik, Jean‐Claude; Galatoire, Olivier; Farah, Edgar; El Methni, Jonathan; Zuber, Kevin; Bergès, Olivier; Savatovsky, Julien; et al.
Abstract : Background: Although several studies have evaluated dynamic contrast‐enhanced (DCE) MRI in the orbit, showing its utility when detecting and diagnosing orbital lesions, none have evaluated the pharmacokinetic models. Purpose: To provide a quality‐based pharmacokinetic model selection for characterizing orbital lesions using DCE‐MRI at 3.0T. Study Type: Prospective. Population: From December 2015 to April 2017, 151 patients with an orbital lesion underwent MRI prior to surgery, including a high temporal resolution DCE sequence, divided into one training and one test dataset with 100 and 51 patients, respectively. Field Strength/Sequence: 3T/DCE. Assessment: Six different pharmacokinetic models were tested. Statistical Tests: Univariate and multivariate analyses were performed using Wilcoxon‐2‐sample tests and a logistic regression to compare parameters between malignant and benign tumors for each pharmacokinetic model for the whole cohort. Receiver operating characteristic (ROC) curve analyses were performed on the training dataset to determine area under curve (AUC) and optimal cutoff values for each pharmacokinetic model, then validated on the test dataset to calculate sensitivity, specificity, and accuracy. Results: Regardless of the model, tissue blood flow and tissue blood volume values were significantly higher in malignant vs. benign lesions: 103.8–195.1 vs. 65–113.8, P [<10 ‐4 –2.10 ‐4 ] and 21.3–36.9 vs. 15.6–33.6, P [<10 ‐4 –0.03] respectively. Extracellular volume fraction and permeability–surface area product or transfer constant appeared to be less relevant: 17.3–27.5 vs. 22.8–28.2, P [0.01–0.7], 1.7–4.9, P [0.2–0.9] and 9.5–38.8 vs. 8.1–22.8, P [<10 ‐4 –0.6], respectively. ROC curves showed no significant differences in AUC between the different models. The two‐compartment exchange (2CX) model ranked first for quality. Data Conclusion: DCE MRI pharmacokinetic model‐derived parameters appeared to be useful for discriminating benign from malignant orbital lesions. The 2CX model provided the best quality of modeling and should be recommended. Perfusion‐related DCE parameters appeared to be significantly more relevant to the diagnostic process. Level of Evidence 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2019;50:1514–1525.